UNVEILING TRAUMA AND IDENTITY: A CRITICAL DISCOURSE ANALYSIS OF LANGUAGE AND IDEOLOGY IN TONI MORRISON’S BELOVED - Ayesha Shahid; Ayesha Izhar Chaudhri; Muhammad Umar Raza; Hafiz Ahmad Bilal (International Journal of Contemporary Issues in Social Sciences, 2024)
This study aims to explore the complex interplay of trauma, identity, and ideology in Toni Morrison’s Beloved through the lens of Critical Discourse Analysis (CDA). By examining the linguistic and narrative structures within the text, this research seeks to uncover how language functions to construct and convey the multifaceted identities of the characters, as well as the underlying ideological frameworks that shape their experiences. Utilizing Fairclough’s three-dimensional model of CDA, this study systematically analyzes the text at three levels: textual, discursive practice, and sociocultural practice. The textual analysis focuses on specific language choices, including vocabulary, metaphors, and narrative techniques, to identify how trauma and identity are articulated. The discursive practice analysis investigates the production and consumption of the text, considering how Morrison’s narrative strategies influence reader interpretations and engagement. The sociocultural practice analysis situates the novel within the broader historical and social contexts of slavery, race, and memory, examining how these contexts inform and are reflected in the text. Through this comprehensive framework, the study elucidates how Beloved not only represents personal and collective trauma but also critiques and challenges dominant ideologies related to race, gender, and history. The findings demonstrate that Morrison’s use of language and narrative structure serves as a powerful tool for both revealing and resisting oppressive ideologies, contributing to a deeper understanding of the novel’s enduring significance and its role in the discourse on identity and memory.